2001
DOI: 10.1007/s004420100656
|View full text |Cite
|
Sign up to set email alerts
|

Fine-root biomass and fluxes of soil carbon in young stands of paper birch and trembling aspen as affected by elevated atmospheric CO2 and tropospheric O3

Abstract: Rising atmospheric CO may stimulate future forest productivity, possibly increasing carbon storage in terrestrial ecosystems, but how tropospheric ozone will modify this response is unknown. Because of the importance of fine roots to the belowground C cycle, we monitored fine-root biomass and associated C fluxes in regenerating stands of trembling aspen, and mixed stands of trembling aspen and paper birch at FACTS-II, the Aspen FACE project in Rhinelander, Wisconsin. Free-air CO enrichment (FACE) was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
171
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(189 citation statements)
references
References 84 publications
17
171
1
Order By: Relevance
“…Increased root growth of forest trees under elevated atmospheric CO 2 has been reported by several researchers (Matamala and Schlesinger, 2000;Pregitzer et al, 2000;King et al, 2001;Pritchard et al, 2001). Consistent findings show that the production and mortality of fine roots produced by trees growing under CO 2 enrichment are significantly increased (Matamala and Schlesinger, 2000;Pregitzer et al, 2000;King et al, 2001;Pritchard et al, 2001).…”
Section: Below-ground Growth and Productivitysupporting
confidence: 80%
See 2 more Smart Citations
“…Increased root growth of forest trees under elevated atmospheric CO 2 has been reported by several researchers (Matamala and Schlesinger, 2000;Pregitzer et al, 2000;King et al, 2001;Pritchard et al, 2001). Consistent findings show that the production and mortality of fine roots produced by trees growing under CO 2 enrichment are significantly increased (Matamala and Schlesinger, 2000;Pregitzer et al, 2000;King et al, 2001;Pritchard et al, 2001).…”
Section: Below-ground Growth and Productivitysupporting
confidence: 80%
“…Consistent findings show that the production and mortality of fine roots produced by trees growing under CO 2 enrichment are significantly increased (Matamala and Schlesinger, 2000;Pregitzer et al, 2000;King et al, 2001;Pritchard et al, 2001). Species differ in the responsiveness of their root systems to increased atmospheric CO 2 , suggesting that differences in the ability of certain species to compete against others could be dramatically changed under elevated CO 2 (Pritchard et al, 2001).…”
Section: Below-ground Growth and Productivitymentioning
confidence: 67%
See 1 more Smart Citation
“…The heterotrophic component of soil respiration is strongly influenced by substrate availability (Raich and Tufekcioglu, 2000;Vasconcelos et al, 2004), which is closely related to aboveground litterfall on a global scale (Raich and Nadelhoffer, 1989;Davidson et al, 2002), and is thus also ultimately driven by aboveground growth and production (Rey et al, 2002). Recently, a microcosm study showed that increased litter inputs under elevated CO 2 would greatly increase microbial respiration in the soil (Liu et al, 2008) and FACE experiments have shown large increases in root respiration, which may be related to increased root biomass or higher specific root respiration rates (Andrews et al, 1999;King et al, 2001;Pregitzer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis of understory biomass, N concentration, N content, atom percent excess 15N, and 15N recovery was performed in SAS (version 8.2, SAS Institute Inc., Cary, NC) using PROC GLM for a split-plot randomized complete block design as detailed in King et al (2001). An alpha level of 0.05 was used and significant differences were further analyzed using least squared means.…”
Section: Laboratory and Statistical Analysesmentioning
confidence: 99%